2013
DOI: 10.1007/s11999-013-3287-x
|View full text |Cite
|
Sign up to set email alerts
|

Is Tibialis Anterior Tendon Transfer Effective for Recurrent Clubfoot?

Abstract: Background Tibialis anterior tendon transfer surgery forms a part of Ponseti management for children with congenital talipes equinovarus who, after initial correction, present with residual dynamic supination. Although retrospective studies support good outcomes, prospective longitudinal studies in this population are lacking. Questions/purposes We assessed strength, plantar loading, ROM, foot alignment, function, satisfaction, and quality of life in patients with clubfoot that recurred after Ponseti casting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
(38 reference statements)
1
23
0
4
Order By: Relevance
“…No patient in this group required subsequent surgical intervention for their clubfoot [38•]. These findings are further supported by other recent studies that demonstrate TATT improves pressure distribution through the foot during gait [39] and restores foot eversion strength [40]. While the data demonstrate TATT is a highly effective tool for preventing relapse of clubfoot, new literature suggests that a second recurrence after TATT can occur in as many as 20 % of patients [41].…”
Section: Tibialis Anterior Tendon Transfersupporting
confidence: 76%
“…No patient in this group required subsequent surgical intervention for their clubfoot [38•]. These findings are further supported by other recent studies that demonstrate TATT improves pressure distribution through the foot during gait [39] and restores foot eversion strength [40]. While the data demonstrate TATT is a highly effective tool for preventing relapse of clubfoot, new literature suggests that a second recurrence after TATT can occur in as many as 20 % of patients [41].…”
Section: Tibialis Anterior Tendon Transfersupporting
confidence: 76%
“…It has been shown that re-routing the lateral half of the AT tendon onto the long axis of the fourth metatarsal was the most effective way [5,21] of correcting the deformity and is confirmed by the authors' clinical experiences. However, others have reported successful results by anchoring the AT tendon to the lateral cuneiform to coincide with the third metatarsal [22,23]. In addition, a single dorsoplantar direction tunnel with tie-over sutures was also found to be clinically effective.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Bununla uyumlu olarak, başlangıçtaki alçılama öncesinde deformitesi daha sert olan, sınıflandırma sistemlerine göre deformite puanı daha yüksek olan ayaklarda, sonradan nüks gelişme oranı gibi, ATG oranları da daha yüksek olarak bulunmuştur. [12] …”
Section: Aşi̇l Tendon Gevşeti̇lmesi̇ (Atg)unclassified
“…[12] Böyle bir ayak, supinasyon deformitesinin sonucunda, yürüyüş sırasında yerle daha az temas eder. Gray ve arkadaşları, [12] temas alanının azlığına karşın arka ayağın ve ayağın lateral kısmının temas süresinin uzadığını bulmuşlardır. Dinamik inversiyon deformitesi, ayağın fonksiyonlarını etkilemek yanında ayakkabı uyumunu da zorlaştırır.…”
Section: Ti̇bi̇ali̇s Anteri̇or Tendon Transferi̇ (Tatt)unclassified